Remark on the EPP in Labeling Theory: Evidence from Romance. (22nd August 2017) - Gallego, Ángel J.
Abstract: This paper puts forward an account of the Extended Projection Principle (EPP) based on Chomsky's (2013, 2015) Labeling Theory. Departing from Chomsky's (2015) proposal, which adopts "feature strength" (Chomsky 1993, 1995), it is suggested that the need for Spec, TP to be occupied by a DP can be attributed to labeling reasons, under the assumption that T is a copy of C (these heads being "bundled" in the lexicon of languages of the English type). Given that copies are inert for computational operations (Chomsky 2000, 2001), it follows that they fail to label (Chomsky 2013), which in turn makes it mandatory for Spec, TP to be filled. This article explores the consequences of this proposal for null‐subject languages, in which C and T are regarded as independent lexical items.